2020
DOI: 10.1126/sciadv.aaz1136
|View full text |Cite
|
Sign up to set email alerts
|

A VersaTile-driven platform for rapid hit-to-lead development of engineered lysins

Abstract: Health care authorities are calling for new antibacterial therapies to cope with the global emergence of antibiotic-resistant bacteria. Bacteriophage-encoded lysins are a unique class of antibacterials with promising (pre)clinical progress. Custom engineering of lysins allows for the creation of variants against potentially any bacterial pathogen. We here present a high-throughput hit-to-lead development platform for engineered lysins. The platform is driven by VersaTile, a new DNA assembly method for the rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
149
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(153 citation statements)
references
References 52 publications
(70 reference statements)
3
149
1
Order By: Relevance
“…VersaTile is a DNA assembly method for the rapid construction of combinatorial libraries of engineered lysins. In a first study, a library of 10 000 engineered lysins was constructed and analyzed to identify a lead candidate 1D10 active against A. baumannii in human serum and in an ex vivo pig burn wound model [44 ].…”
Section: Equipping Lysins With Antibacterial Activity By Protein Engimentioning
confidence: 99%
“…VersaTile is a DNA assembly method for the rapid construction of combinatorial libraries of engineered lysins. In a first study, a library of 10 000 engineered lysins was constructed and analyzed to identify a lead candidate 1D10 active against A. baumannii in human serum and in an ex vivo pig burn wound model [44 ].…”
Section: Equipping Lysins With Antibacterial Activity By Protein Engimentioning
confidence: 99%
“…The reference-based genome assembly obtained using bwa-mem was chosen for analysis, due to higher genome coverage and less number of indels and misassemblies compared to the reference genome. Although earlier studies have shown that bacterial MinION sequences show high mapping rates to the reference genome, with fewer indel rates, bwa-mem has found limited application with long error-prone reads [51][52][53][54] . We show that it is possible to obtain assemblies with good genome coverage for AMR determinant detection by using nanopore-only reads with a reference-based genome assembly, without depending on additional Illumina sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…From all animal skin types, porcine skin resembles human skin the most, making them most suitable for skin and wound research (Abdullahi et al 2014). However, only ex vivo pig skin models have been implemented so far in the lysin field (Nithya et al 2018;Gerstmans et al 2020). Practical and financial considerations often explain the choice for a murine model (Zomer and Trentin 2018).…”
Section: Advanced Formulation Strategies: Towards Integrated Topical mentioning
confidence: 99%
“…This was illustrated by R€ ohrig and colleagues who performed a preceding screening of enzyme variants under intracellular and lysosomal conditions before different fusions with CPPs were attempted (R€ ohrig et al 2020). Whereas the authors could rely on an available library, the VersaTile approach (Gerstmans et al 2020) could further leverage this process by increasing library complexity by incorporating more CPPs, more CBDs, EADs, or other elements of interest. It is clear that many concepts that are highlighted in this review can benefit from such libraries of increased complexity, but following the first law of directed evolution ("you get what you screen for"), the screening assays must be carefully selected and/or combined given the observed discrepancies between different in vitro and in vivo assays (Schmidt-Dannert and Arnold 1999; Peisajovich and Tawfik 2007).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation